Competition, financial innovation and commercial bank loan portfolios - Zarutskie, Rebecca (Journal of Financial Intermediation, 2013)
I examine how US commercial bank loan portfolios change in response to the rise of securitization markets and banking market deregulations over 1976–2003. Banks increasingly tilt their portfolios toward real-estate-backed loans. However, there are significant differences across banks. Larger banks and younger banks disproportionately shift their lending toward real-estate-backed loans, particularly commercial real-estate-backed loans, whereas smaller banks and older banks maintain greater shares of their loan portfolios in commercial and personal loans. When larger banks make more real-estate-backed loans, they charge lower interest rates, consistent with these banks lowering the costs of lending and expanding credit for borrowers. In contrast, smaller banks charge higher interest rates, consistent with these banks restricting lending to a select group of borrowers.